1962
DOI: 10.1152/ajplegacy.1962.203.5.782
|View full text |Cite
|
Sign up to set email alerts
|

A central nervous system component of epinephrine hyperglycemia

Abstract: At least half the hyperglycemic response (in hepatic venous blood) to intravenous epinephrine was found to be dependent on the integrity of the medulla oblongata caudal to the cerebellar peduncles. Transection of the medulla at the level of the fovea inferior unmasked a vagus-mediated hypoglycemic response to epinephrine. Changes in blood glucose concentration after epinephrine administration were independent of blood pressure and the base-line blood glucose levels. Microinjections of epinephrine into the floo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1963
1963
1986
1986

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…There is evidence that the splanchnic nerves exert direct neural control over liver phosphorylase [1,15,16], as discussed later. Rosenberg and DiStefano [17] and Ezdinli et al [18] have also shown that the hyperglycaemia induced by systemic administration of epinephrine is inhibited by section of the medulla or the spinal cord. However, the influence of glycogenolytic hormones, particularly pancreatic hormones, on phosphorylase activation after hypothalamic stimulation has to be taken into account.…”
Section: Hypothalamo-hepatic Axis In the Control Of Carbohydrate Metamentioning
confidence: 96%
“…There is evidence that the splanchnic nerves exert direct neural control over liver phosphorylase [1,15,16], as discussed later. Rosenberg and DiStefano [17] and Ezdinli et al [18] have also shown that the hyperglycaemia induced by systemic administration of epinephrine is inhibited by section of the medulla or the spinal cord. However, the influence of glycogenolytic hormones, particularly pancreatic hormones, on phosphorylase activation after hypothalamic stimulation has to be taken into account.…”
Section: Hypothalamo-hepatic Axis In the Control Of Carbohydrate Metamentioning
confidence: 96%
“…The complex mechanism of E hyperglycemia [14] also includes a neurogenic component. It has been postulated that the hyperglycemic center in the floor of the fourth ventricle contains E sensitive receptors [17] and the efferent pathway of this reflex descends in the thoraco-cervical sympathetic tract to the thy roid gland [6]. We assume that bretylium prevented the hyperglycemic re sponse by blocking the efferent (adrenergic) pathway.…”
Section: Effect Of Hemorrhage On Bretylium-medicated Sheepmentioning
confidence: 85%
“…Since it had been suggested that epinephrine may stimulate glucagon secretion [10,26,32], it became necessary to observe the effects of epi nephrine in glucagon-free animals. Partial evisceration was chosen as a simple and efficient way to remove the source of glucagon.…”
Section: Effect Of Epinephrine On Acpc Uptake In Fasted Eviscerated mentioning
confidence: 99%
“…Sergeyeva [32] showed that there is a change in the population of a-and /9-cells in the pancreatic islets of cats after inject ing epinephrine. R osenberg and Di Stefano [26] identified a CNS com ponent to epinephrine-induced hyperglycemia and suggested that a neural pathway from the fourth ventricle of the brain to the pancreas is involved in epinephrine-induced hyperglycemia and further suggested that epi nephrine stimulates the CNS in the medullary region thereby causing an impulse to be initiated which travels to the pancreas where the a-cells are stimulated to release glucagon. In 1966 Ezdinli and Sokal [10] studied the comparative effects of epinephrine and glucagon on liver glycogen metabolism in dogs and concluded that the injection of epinephrine caused an increase in glucagon secretion.…”
Section: Hypothesis No 3: Adrenal-pancreas Involvement -Glucagon Secmentioning
confidence: 99%